TRANSFORMASI DIGITAL DALAM KOMUNIKASI MEDIA MASSA: STUDI KASUS TVRI SUMATERA SELATAN - Muhammad Hidayatul Fikri; Putri Citra Hati (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This study aims to investigate the significant impact of digital transformation in mass media communication, with a focus on the case study of TVRI South Sumatra. Digital transformation has fundamentally changed the role of mass media in society. Mass media is no longer merely a passive conveyer of information but has become an interactive, participatory, and dynamic platform. In this context, several communication theories can be used as a framework to understand the transformation of mass media in this digital era. One of them is the Agenda Setting Theory, which posits that mass media has the power to determine the agenda of topics considered important by the public by highlighting specific issues. In the digital age, this transformation affects how TVRI South Sumatra, as a regional media station, responds to and addresses changes in the attention and needs of its audience. The primary research question of this study is, "How does TVRI South Sumatra respond to the digital transformation in mass media communication?" This question reflects the need to understand how the station adapts to the changing trends in media consumption that are increasingly shifting toward digital media.